Subphenotypes of SARS-CoV-2-Associated ARDS Overlap Each Other: A Retrospective Analysis - Nair, Parvathy R.; Girish, Kavitha; Mini, Gouri; Khan, Tazeen; Haritha, Damarla; Sanyal, Koninica; Bhattacharjee, Sulagna; Baidya, Dalim K.; Ray, Bikash R.; Anand, Rahul K.; Datta, Sudip K.; Soneja, Manish; Subramaniam, Rajeshwari; Maitra, Souvik (Journal of Laboratory Physicians, 2023)
Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus-associated pneumonia and acute respiratory distress syndrome (ARDS) were often associated with hyperinflammation and elevation of several serum inflammatory markers but usually less than what is observed in non-coronavirus disease (COVID) ARDS. Elevated inflammatory markers such as C-reactive protein, interleukin (IL)-6, etc., are associated with severe infection. This study identified subphenotypes of COVID-19 ARDS patients by latent profile analysis in a cohort of Indian patients.Methods Data of n = 233 adult Indian patients with laboratory-confirmed SARS-CoV-2 infection admitted to a tertiary care teaching hospital were analyzed in this retrospective study. Only patients with acute respiratory failure (defined by partial pressure of oxygen/fraction of inspired oxygen ratio < 200 mm Hg) and chest X-ray showing bilateral infiltrates were included.Results The patients' mean (standard deviation) age was 53.3 (14.9) years, and 62% were male. A two subphenotypic model was formulated based on the lowest Bayesian information criterion. Neutrophil-to-lymphocyte ratio and serum IL-6 were latent variables in that model (entropy 0.91). The second phenotype (hyperinflammatory) had lower platelet count (p = 0.02), higher serum creatinine (p = 0.004), higher C-reactive protein (p = 0.001), higher ferritin (p < 0.001), and serum lactate dehydrogenase (p = 0.009). Age-adjusted hospital mortality (p = 0.007), duration of hospital stay (p < 0.001), and duration of intensive care unit stay (p < 0.001) were significantly higher in the second subphenotype.Conclusion Two distinct but overlapping subphenotypes were identified in SARS-CoV-2-associated respiratory failure. Hyperinflammatory subphenotype was associated with significantly poor short-term outcomes.
Keywords: ARDS; COVID-19; SARS-CoV-2; latent class